Microbial decontamination of maca (Lepidium meyenii) applying organic sterilization system (OSS) to preserve its nutritional and sensory properties - Guevara, Américo (2016)
The research aimed to apply the system of organic sterilization (OSS) in maca, determining the process parameters: time and temperature steam injection saturated reduce the count of aerobic microorganisms, molds, yeasts, E. coli, Salmonella and coliform total, and evaluating the influence of process in total glucosinolate content. The maximum microbial decontamination of maca was achieved by applying a load of 5 kg/pouch for 6 min. With a temperature of 100 °C saturated steam injection. Under these conditions, the reduction of the microbial load was 99,9 % (< 10 UFC/g), 50% (< 10 UFC/g) and 93,3% (< 10 UFC/g) for aerobic, molds, and yeasts, respectively; pathogen behavior was very similar to that of the raw material: E. coli < 3 UFC/g, absence of salmonella (25 g) and < 3 UFC/g for total coliforms. Glucosinolate content was maintained during the process in 1,5 μmol/g, which showed that by applying the OSS technology is achieved by preserving the functional, sensory and nutritional quality of maca.